Educating Student Teachers to Become High Quality Professionals – A Finnish Case - Hannele Niemi (Center for Educational Policy Studies Journal)
For decades, the Finnish orientation toward teacher education has committed itself to the development of an inquiry oriented and research-based professional culture. The aims of teacher education are to train students to find and analyse problems they may expect to face in their future work. This study consists of a survey of student teachers (n=545) in two universities in Finland. Web-based surveys with quantitative and qualitative questions were sent to all student teachers in the beginning of May 2010. Students assessed how teacher education had provided them with the competences they need in a high standard profession, what kinds of active learning experiences they had in their TE studies, and how research studies of teacher education had contributed to their professional development. The participants of the study assessed that they had achieved good skills in planning teaching and curricula. They were capable of using different teaching methods. They were aware of their own teaching philosophy and their responsibilities as professionals and life-long learners. They consider the research component of TE valuable to their independent and critical thinking. They were very engaged in studies. Finnish pre-service teacher education seems to function very well and to be effective in providing the skills teachers need to work as independent professionals. The results of the study show, however, that students also need more supervision and guidance on how to collaborate with parents and other stakeholders outside school, such as representatives of working life as well as partners in business life and culture.